A research study on the job satisfaction of employees in B. Braun Medical Supplies Sdn. Bhd. / Nurliyana Anuar Khan - Anuar Khan, Nurliyana (Faculty of Business and Management, 2017)
The purpose of this research is to study the main reason of job satisfaction of employees in B. Braun Medical Supplies Sdn. Bhd. In this study, the researcher chooses to use three independent variables which are physical environment (IV1), human environment (IV2), and organizational environment (IV3) and its relation to dependent variable which is Job Satisfaction (DV). A survey questionnaire is distributed to 95 employees as a sample size. This research uses a simple random sampling technique. The quantitative data in this research is analyzed by descriptive statistics using the Statistical Package for Social Sciences Software (SPSS).